Hydrous titanium oxide with anion-trapping function and manufacturing method thereof
Patent Information
- Application Number
- JP2022155887
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-10-15
- Filing Date
- 2022-09-29
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing hydrous titanium oxides exhibit insufficient anion trapping functions due to inadequate specific surface area, total pore volume, and ion trapping capacities, which affect their performance in encapsulant resin compositions for electronic components.
Hydrous titanium oxide with a specific surface area of 100 m²/g or more and total pore volume of 0.2 cm³/g or more, characterized by the absence of a diffraction peak at 25.3±0.5° and a weight loss rate difference of ≤15%, along with controlled impurity levels and optional silicon compound blending or coating, is produced through specific precipitation, filtration, drying, and pulverization processes.
The resulting hydrous titanium oxide demonstrates enhanced anion trapping capabilities, particularly for sulfate, chloride, nitrate, phosphate, and acetate ions, and provides improved corrosion resistance and viscosity control when integrated into resin compositions.
Abstract
Description
[Technical Field]
[0001] The present invention relates to hydrated titanium oxide having anion-scavenging function and a method for producing the same. [Background technology]
[0002] Electronic components such as semiconductor devices are often sealed using resin compositions for sealing materials, and such compositions are known to contain various materials in addition to epoxy resin. Patent Document 1 describes a flame-retardant resin composition for sealing electronic components, characterized by comprising at least one inorganic anion exchanger selected from hydrated zirconium oxide and hydrated titanium oxide, epoxy resin, curing agent, inorganic filler, and red phosphorus-based flame retardant. According to this, it is a flame-retardant resin composition for sealing electronic components that exhibits excellent flame retardancy and high moisture resistance reliability without using some or all halogen compounds and antimony compounds. Furthermore, the inorganic anion exchanger contained in the resin composition is said to capture anionic impurities in the resin composition and function to maintain the performance of the sealing material for a long period of time.
[0003] Furthermore, as a method for removing sulfate ions, Patent Document 2 describes a method for removing sulfate ions from an aqueous alkali metal chloride solution, characterized by contacting an aqueous alkali metal chloride solution containing sulfate ions with titanium hydroxide in a slurry state under acidic conditions, thereby adsorbing the sulfate ions in the aqueous solution onto the titanium hydroxide through an ion exchange reaction, separating the titanium hydroxide with the adsorbed sulfate ions from the aqueous solution, and then dispersing it in another aqueous solution and reacting it with alkali to desorb the sulfate ions into the aqueous solution. According to this method, since only sulfate ions can be selectively removed from salt water using hydrochloric acid and alkali hydroxide, it has the advantage of being less expensive than conventional methods. However, as in Patent Documents 1 and 2, even with hydrated titanium oxide that captures anions such as sulfate ions, the anion capture function may be insufficient depending on the physical properties of the hydrated titanium oxide, and further improvements have been needed. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2003-147168 [Patent Document 2] Japanese Patent Application Publication No. 4-338110 [Overview of the project] [Problems that the invention aims to solve]
[0005] The present invention was made to solve the above problems, and aims to provide a hydrated titanium oxide with a large specific surface area and a total pore volume above a certain level, which has excellent anion-capturing function and can be contained in a resin composition for sealing materials. [Means for solving the problem]
[0006] The above problem is a hydrated titanium oxide having anion-scavenging function, with a specific surface area of 100 m². 2 The amount is greater than or equal to / g, and the total pore volume is 0.2 cm³. 3 This problem is solved by providing hydrated titanium oxide characterized by having a content of 1 / g or more.
[0007] In this case, it is preferable that, in the X-ray diffraction measurement, no diffraction peak intensity is detected at a diffraction angle (2θ) of 25.3±0.5°, or that the full width at half maximum of the diffraction peak at a diffraction angle (2θ) of 25.3±0.5° is 1.0° or more, and that the average secondary particle diameter is 100 μm or less.
[0008] In a preferred embodiment, the weight loss rate A, calculated from the weight after holding at 100°C for 2 hours based on the weight before heating, and the weight loss rate B, calculated from the weight after holding at 250°C for 2 hours, are both hydrated titanium oxide that satisfies the following formula (I). BA ≤ 15 (I)
[0009] It is preferable that the content of ionic impurities is 4.0% by weight or less, or the chlorine content is 200 ppm or less, it is preferable that the sulfate ion capture capacity is 0.20 meq / g or more, and it is preferable that the chloride ion capture capacity is 0.02 meq / g or more. A preferred embodiment is one in which a silicon compound is blended, and a preferred embodiment is one in which it is coated with a silicon compound. Also, a preferred embodiment is that it is a resin composition for a sealing material containing the titanium hydroxide hydrate.
[0010] Further, the above problem is solved by providing a method for producing titanium hydroxide hydrate, which comprises using a titanium-containing acidic aqueous solution as a starting material, mixing the titanium-containing acidic aqueous solution with water at 5 to 98 °C and a basic aqueous solution to obtain a titanium hydroxide hydrate precipitate, filtering the titanium precipitate, washing it until the conductivity of the filtrate becomes 2000 μS / cm or less, drying it at 100 to 450 °C, and pulverizing the dried titanium hydroxide hydrate powder.
[0011] Furthermore, the above problem is solved by providing a method for producing titanium hydroxide hydrate, which comprises using titanium alkoxide as a starting material, adding water to an alcohol mixed solution containing the titanium alkoxide so that the molar ratio of water to titanium alkoxide (water / titanium alkoxide) is 0.1 or more to obtain a titanium hydroxide hydrate precipitate, filtering the precipitate, drying it at 60 to 450 °C, and pulverizing the dried titanium hydroxide hydrate powder.
Advantages of the Invention
[0012] According to the present invention, it is possible to provide titanium hydroxide hydrate having a large specific surface area, a total pore volume of a certain level or more, and excellent anion capture function. Since the titanium hydroxide hydrate has an excellent corrosion prevention effect, it can be suitably used as a resin composition for a sealing material containing the titanium hydroxide hydrate.
Embodiments for Carrying Out the Invention
[0013] The titanium hydroxide hydrate of the present invention is a titanium hydroxide hydrate having an anion capturing function, with a specific surface area of 100 m 2 / g or more, and a total pore volume of 0.2 cm 3 / g or more. By satisfying such a configuration where the specific surface area is a certain value or more and the total pore volume is a certain value or more, it has become clear that a titanium hydroxide hydrate excellent in the anion capturing function can be obtained. As is clear from the comparison between the examples and comparative examples described later, in the comparative example where the specific surface area is less than 100 m 2 / g, the sulfate ion capturing capacity is 0.19 meq / g or less and the chloride ion capturing capacity is 0.01 meq / g or less, and the anion capturing function is insufficient. On the other hand, in the examples where the specific surface area is a certain value or more and the total pore volume is a certain value or more, even the lowest sulfate ion capturing capacity is 0.23 meq / g and even the lowest chloride ion capturing capacity is 0.05 meq / g, indicating that it is a titanium hydroxide hydrate excellent in the anion capturing function.
[0014] In the titanium hydroxide hydrate of the present invention, when the sulfate ion capturing capacity is less than 0.20 meq / g, the anion capturing function becomes insufficient. Therefore, it is preferably 0.20 meq / g or more, more preferably 0.50 meq / g or more, still more preferably 0.80 meq / g or more, particularly preferably 1.10 meq / g or more, and most preferably 1.30 meq / g or more. The sulfate ion capturing capacity is usually 10 meq / g or less. The sulfate ion capturing capacity can be measured by the method described in the examples below.
[0015] [[ID=1*3]] In the hydrated titanium oxide of the present invention, if the chloride ion capture capacity is less than 0.02 meq / g, the anion capture function becomes insufficient. Therefore, it is preferable that the chloride ion capture capacity is 0.02 meq / g or more, more preferably 0.06 meq / g or more, even more preferably 0.10 meq / g or more, particularly preferably 0.15 meq / g or more, and most preferably 0.25 meq / g or more. The chloride ion capture capacity is usually 2 meq / g or less. The chloride ion capture capacity can be measured by the method described in the examples below.
[0016] In the hydrated titanium oxide of the present invention, if the nitrate ion capture capacity is less than 0.02 meq / g, the anion capture function becomes insufficient. Therefore, it is preferable that the nitrate ion capture capacity be 0.02 meq / g or more, more preferably 0.05 meq / g or more, even more preferably 0.10 meq / g or more, particularly preferably 0.12 meq / g or more, and most preferably 0.20 meq / g or more. The nitrate ion capture capacity is usually 2 meq / g or less. The nitrate ion capture capacity can be measured by the method described in the examples below.
[0017] In the hydrated titanium oxide of the present invention, if the phosphate ion capture capacity is less than 0.20 meq / g, the anion capture function becomes insufficient. Therefore, it is preferable that the phosphate ion capture capacity is 0.20 meq / g or more, more preferably 0.50 meq / g or more, even more preferably 0.80 meq / g or more, particularly preferably 1.10 meq / g or more, and most preferably 1.30 meq / g or more. The phosphate ion capture capacity is usually 10 meq / g or less. The phosphate ion capture capacity can be measured by the method described in the examples below.
[0018] In the titanium hydroxide hydrate of the present invention, when the acetic acid ion capture capacity is less than 0.02 meq / g, the anion capture function becomes insufficient. Therefore, the acetic acid ion capture capacity is preferably 0.02 meq / g or more, more preferably 0.04 meq / g or more, still more preferably 0.10 meq / g or more, particularly preferably 0.12 meq / g or more, and most preferably 0.15 meq / g or more. The acetic acid ion capture capacity is usually 1 meq / g or less. The acetic acid ion capture capacity can be measured by the method described in the examples below.
[0019] In the titanium hydroxide hydrate of the present invention, the specific surface area is 100 m 2 / g or more. When the specific surface area is less than 100 m 2 / g, the anion capture function becomes insufficient. The specific surface area is preferably 140 m 2 / g or more, more preferably 170 m 2 / g or more, still more preferably 200 m 2 / g or more, particularly preferably 250 m 2 / g or more, and most preferably 310 m 2 / g or more. On the other hand, from the viewpoint of suppressing a significant increase in viscosity when the titanium hydroxide hydrate is blended into the resin composition for the sealing material, the specific surface area is preferably 550 m 2 / g or less, more preferably 520 m 2 / g or less, still more preferably 480 m 2 / g or less, particularly preferably 450 m 2 / g or less. The specific surface area (m 2 [[ID=If the value is less than / g, the anion capture function will be insufficient. The total pore volume is 0.3 cm³. 3 It is preferable that it be 0.4 cm or more. 3 It is more preferable that it be 0.6 cm or more. 3 It is even more preferable that it be 0.8 cm or more. 3 It is particularly preferable that the amount is 1 / g or more. On the other hand, the total pore volume is usually 2.5 cm³. 3 It is less than / g and 2.2cm 3 It is preferable that the total pore volume (cm³) in the present invention is less than or equal to / g. 3 The value of N2 ( / g) can be determined by converting the amount of N2 gas adsorbed at a relative pressure of p / p0 to the volume of N2 in liquid state.
[0021] In the hydrated titanium oxide of the present invention, it is preferable that the average secondary particle diameter is 100 μm or less. If the average secondary particle diameter exceeds 100 μm, scratches originating from the hydrated titanium oxide may occur when it is incorporated into a resin composition. Therefore, the average secondary particle diameter is more preferably 90 μm or less, even more preferably 60 μm or less, particularly preferably 45 μm or less, and most preferably 35 μm or less. On the other hand, the average secondary particle diameter is usually 1 μm or more, preferably 4 μm or more, and more preferably 6 μm or more. In the present invention, the average secondary particle diameter is determined by measuring the particle size distribution and calculating the 50% volume cumulative particle size from the obtained particle size distribution, as described in the examples below.
[0022] In the present invention, a preferred embodiment satisfies the following conditions when performing X-ray diffraction measurements on hydrated titanium oxide: either no diffraction peak intensity is detected at a diffraction angle (2θ) of 25.3±0.5°, or the full width at half maximum (FWHM) of the diffraction peak at a diffraction angle (2θ) of 25.3±0.5° is 1.0° or greater. Here, "no diffraction peak intensity detected" means that the peak intensity is 200 counts or less. As is clear from the comparison between the examples and comparative examples described later, in the comparative example where the FWHM of the diffraction peak at a diffraction angle (2θ) of 25.3±0.5° was 0.9° or less, the anion trapping function was insufficient, whereas in the example where no diffraction peak intensity is detected at a diffraction angle (2θ) of 25.3±0.5°, or the FWHM of the diffraction peak at a diffraction angle (2θ) was 1.0° or greater, the anion trapping function was excellent. Therefore, a preferred embodiment of the present invention is a hydrated titanium oxide that satisfies the following conditions: when X-ray diffraction measurements are performed, no diffraction peak intensity is detected at a diffraction angle (2θ) of 25.3±0.5°, or the full width at half maximum (FWHM) of the diffraction peak at a diffraction angle (2θ) of 25.3±0.5° is 1.0° or greater. Note that orthotitanic acid is a hydrated titanium oxide that satisfies the following conditions: when X-ray diffraction measurements are performed, no diffraction peak intensity is detected at a diffraction angle (2θ) of 25.3±0.5°. Furthermore, the FWHM of the diffraction peak at a diffraction angle (2θ) of 25.3±0.5° is more preferably 1.1° or greater, and even more preferably 1.2° or greater. This FWHM is usually 2.0° or less.
[0023] In the present invention, a preferred embodiment is one in which the weight loss rate A, calculated from the weight after holding at 100°C for 2 hours based on the weight before heating, and the weight loss rate B, calculated from the weight after holding at 250°C for 2 hours, satisfy the following formula (I). BA ≤ 15 (I)
[0024] If the difference in weight loss rate BA in formula (I) above exceeds 15, when it is incorporated into a resin composition, voids may be created due to the crystal water contained in the hydrated titanium oxide, which may have an adverse effect. It is more preferable that BA in formula (I) above be 14 or less, even more preferable that it be 13 or less, and particularly preferable that it be 10 or less. On the other hand, BA in formula (I) above is usually 0.1 or more.
[0025] In the hydrated titanium oxide of the present invention, it is preferable that the content of ionic impurities is 4.0% by weight or less. In the present invention, ionic impurities refer to at least one selected from the group consisting of anions such as sulfate ions, chloride ions, nitrate ions, and carbonate ions, and cations such as sodium ions, potassium ions, magnesium ions, and lithium ions. If the content of ionic impurities exceeds 4.0% by weight, the corrosion prevention effect may not be obtained. Therefore, the content of ionic impurities is more preferably 3.0% by weight or less, even more preferably 2.0% by weight or less, particularly preferably 1.0% by weight or less, and most preferably 0.5% by weight or less. On the other hand, the content of ionic impurities is usually 0.01% by weight or more. The anions in the above ionic impurities are determined by ion chromatography, and the cations are determined by ICP emission spectrometry.
[0026] In the hydrated titanium oxide of the present invention, the chlorine content is preferably 200 ppm or less. If the chlorine content exceeds 200 ppm, the corrosion prevention effect may not be obtained, and the chlorine content is more preferably 180 ppm or less, even more preferably 150 ppm or less, and particularly preferably 120 ppm or less. On the other hand, the chlorine content is usually 10 ppm or more.
[0027] In the present invention, a preferred embodiment of the hydrated titanium oxide is that it contains a silicon compound, and a more preferred embodiment is that the hydrated titanium oxide is coated with a silicon compound. By adding or coating it with a silicon compound in this way, the hydrated titanium oxide becomes hydrophobic, which suppresses the increase in viscosity when it is incorporated into a resin composition. The amount of silicon compound used for coating is preferably 0.2 to 20 parts by weight, and more preferably 1 to 15 parts by weight, per 100 parts by weight of hydrated titanium oxide. The silicon compound is not particularly limited, and known compounds can be used.
[0028] The hydrated titanium oxide of the present invention may contain other components, as long as they do not hinder the effects of the present invention. For example, components derived from the raw materials used to produce hydrated titanium oxide can be included. Niobium (Nb) is one such component derived from the aqueous solution of titanyl sulfate, which is a raw material, and the content of such niobium (Nb) is preferably 2.0 mol% or less.
[0029] The method for producing hydrated titanium oxide according to the present invention is not particularly limited. The hydrated titanium oxide of the present invention can be suitably obtained by following these steps in order: using a titanium-containing acidic aqueous solution as a starting material; mixing the titanium-containing acidic aqueous solution with water at 5 to 98°C and a basic aqueous solution to obtain a hydrated titanium oxide precipitate (hereinafter sometimes abbreviated as "neutralization step 1"); filtering the precipitate and washing it until the conductivity of the filtrate is 2000 μS / cm or less (hereinafter sometimes abbreviated as "filtration and washing step 1"); drying it at 100 to 450°C (hereinafter sometimes abbreviated as "drying step 1"); and grinding the dried hydrated titanium oxide powder (hereinafter sometimes abbreviated as "grinding step 1").
[0030] For the titanium-containing acidic aqueous solution used in neutralization step 1, aqueous solutions containing titanium compounds such as titanyl sulfate, titanium tetrachloride, titanium nitrate, and titanium acetate are preferably used. For the basic aqueous solution, aqueous ammonia, aqueous sodium hydroxide, aqueous sodium carbonate, ethylamine, diethylamine, triethylamine, triethanolamine, ethylenediamine, and tert-butylamine are preferably used. The concentration of the titanium compound in the titanium-containing acidic aqueous solution is preferably 50 to 350 g / L as TiO2. In neutralization step 1, a hydrated titanium oxide precipitate is obtained by mixing the titanium-containing acidic aqueous solution with water at 5 to 98°C and a basic aqueous solution. From the viewpoint of obtaining hydrated titanium oxide with a large specific surface area and a total pore volume above a certain level, a preferred embodiment is to dropwise add the titanium-containing acidic aqueous solution and the basic aqueous solution simultaneously over a certain period of time while stirring the water at 5 to 98°C, maintaining a pH of 7 to 9 for each solution. From the viewpoint of obtaining hydrated titanium oxide with a larger specific surface area and a total pore volume above a certain level, the pH is more preferably 7.2 or higher, even more preferably 7.3 or higher, and particularly preferably 7.4 or higher. On the other hand, the pH is more preferably 8.6 or lower, even more preferably 8.2 or lower, particularly preferably 7.9 or lower, and most preferably 7.7 or lower. Furthermore, the certain time is not particularly limited, but 10 minutes to 12 hours is preferred, 12 minutes to 10 hours is more preferred, and 1 to 5 hours is even more preferred. At this time, the water used is preferably deionized water, distilled water, or pure water, and the titanium-containing acidic aqueous solution and the basic aqueous solution are mixed while maintaining the water temperature at 5 to 98°C. From the viewpoint of obtaining hydrated titanium oxide with a large specific surface area, the temperature is preferably 10°C or higher, more preferably 20°C or higher, even more preferably 40°C or higher, particularly preferably 60°C or higher, and most preferably 80°C or higher.
[0031] In neutralization step 1, from the viewpoint of suppressing particle growth and obtaining hydrated titanium oxide with a high specific surface area and high pore volume, the solid content concentration of the slurry after neutralization is preferably 20% or less, more preferably 15% or less, and even more preferably 10% or less. On the other hand, the solid content concentration of the slurry is usually 1% or more, and preferably 2% or more. The solid content concentration of the slurry is determined by calculating it from the dry solid content measured under dry conditions at 100°C.
[0032] In the filtration and washing step 1, it is preferable to filter the hydrated titanium oxide precipitate obtained in the neutralization step 1 by a known method and wash it until the conductivity of the filtrate is 2000 μS / cm or less. Washing until the conductivity of the filtrate is 2000 μS / cm or less has the advantage of yielding hydrated titanium oxide with excellent anion capture function and corrosion prevention effect. The conductivity is more preferably 1500 μS / cm or less, even more preferably 1000 μS / cm or less, particularly preferably 650 μS / cm or less, and most preferably 500 μS / cm or less.
[0033] In drying step 1, it is preferable to dry at 100 to 450°C to obtain hydrated titanium oxide powder. This reduces the amount of crystalline water contained in the hydrated titanium oxide, thereby reducing the value of BA, which is the difference in weight loss rates in formula (I) above. This has the advantage of preventing voids from forming and adversely affecting the resin composition when it is incorporated. If the drying temperature is below 100°C, the value of BA, which is the difference in weight loss rates in formula (I) above, becomes large, and there is a risk that voids will form and adversely affect the resin composition when it is incorporated. From this viewpoint, the drying temperature is preferably 120°C or higher, more preferably 150°C or higher, and even more preferably 250°C or higher. On the other hand, if the drying temperature exceeds 450°C, the specific surface area becomes small, and the full width at half maximum of the diffraction peak with a diffraction angle (2θ) of 25.3±0.5° also falls below a certain level, which may reduce the anion trapping function. From this viewpoint, the drying temperature is more preferably 450°C or lower, and even more preferably 350°C or lower.
[0034] In the grinding step 1, it is preferable to grind the dried hydrated titanium oxide powder using a known grinder or the like. The grinder is not particularly limited, and ultracentrifugal grinders, ball mills, jet mills, lithographs, etc., can be used. By grinding, hydrated titanium oxide with an average secondary particle diameter of a certain value or less can be obtained, and the average secondary particle diameter value described above is preferably adopted. When grinding with an ultracentrifugal grinder, it is preferable to grind at a rotor speed of 4000 rpm or higher, more preferably 7000 rpm or higher, even more preferably 9000 rpm or higher, and particularly preferably 13000 rpm or higher.
[0035] In the present invention, a preferred embodiment is one in which a silicon compound is incorporated into the hydrated titanium oxide. The timing of incorporating the silicon compound is not particularly limited and can be appropriately incorporated after the neutralization step 1, after the filtration / washing step 1, or after the drying step 1. In particular, it is preferable to incorporate the silicon compound after the filtration / washing step 1 or after the drying step 1, and it is more preferable to incorporate the silicon compound after the drying step 1. The silicon compound used is not particularly limited and any known compound can be used.
[0036] Furthermore, as a method for producing hydrated titanium oxide according to the present invention, the hydrated titanium oxide of the present invention can also be suitably obtained by following these steps in order: using titanium alkoxide as a starting material, adding water to an alcohol mixed solution containing titanium alkoxide so that the molar ratio of titanium alkoxide to water (water / titanium alkoxide) is 0.1 or more to obtain a hydrated titanium oxide precipitate (hereinafter sometimes abbreviated as "neutralization step 2"), filtering the precipitate (hereinafter sometimes abbreviated as "filtration step 2"), drying at 60 to 450°C (hereinafter sometimes abbreviated as "drying step 2"), and grinding the dried hydrated titanium oxide powder (hereinafter sometimes abbreviated as "grinding step 2").
[0037] In neutralization step 2, it is preferable to add water to the alcohol mixed solution containing titanium alkoxide so that the molar ratio of titanium alkoxide to water (water / titanium alkoxide) is 0.1 or higher to obtain a hydrated titanium oxide precipitate. This reduces the amount of crystalline water contained in the hydrated titanium oxide, thereby reducing the value of BA, which is the difference in weight loss rate in formula (I) above, and has the advantage of preventing the formation of voids that would adversely affect the resin composition when it is incorporated. If the molar ratio (water / titanium alkoxide) is less than 0.1, there is a risk that a hydrated titanium oxide precipitate cannot be obtained, and it is more preferable that the molar ratio (water / titanium alkoxide) is 0.15 or higher, even more preferable that it is 0.2 or higher, and particularly preferable that it is 0.25 or higher. On the other hand, the molar ratio (water / titanium alkoxide) is usually 10 or less, preferably 8 or less, more preferably 6 or less, and even more preferable that it is 4 or less. Examples of titanium alkoxides that can be used include titanium tetraethoxide, titanium tetraisopropoxide, and titanium tetra-n-butoxide.
[0038] In filtration step 2, it is preferable to filter the hydrated titanium oxide precipitate obtained in neutralization step 2 by a known method and then perform drying step 2, which involves drying at 60 to 450°C. Next, it is preferable to perform grinding step 2, which involves grinding the dried hydrated titanium oxide powder with a known grinder or the like. For grinding step 2, the same method as in grinding step 1 is preferably employed.
[0039] The hydrated titanium oxide obtained as described above provides a hydrated titanium oxide with a large specific surface area and a total pore volume above a certain level, exhibiting excellent anion capture function. Because this hydrated titanium oxide has excellent corrosion prevention effects, it can be suitably used as a resin composition for sealing materials containing this hydrated titanium oxide. [Examples]
[0040] The present invention will be described in more detail below using examples.
[0041] (1) Specific surface area, total pore volume The specific surface area and total pore volume were measured using the "BELSORP mini" manufactured by Microtrac-Bel Corporation. Before measurement, the hydrated titanium oxide was heated under vacuum as a pretreatment to remove moisture and other substances physically adsorbed onto it.
[0042] (2) Full width at half maximum of the X-ray diffraction peak The full width at half maximum (FWHM) of X-ray diffraction peaks was measured using PANalytical's "X'pert-PRO" system. Measurements were performed using Cu-Kα rays under conditions of X-ray output of 45kV and 40mA. The FWHM of 25.3±0.5° X-ray diffraction peaks from the obtained diffraction patterns was calculated. Peaks with an intensity of 200 counts or less were classified as undetectable.
[0043] (3) Average secondary particle diameter The average secondary particle size of hydrated titanium dioxide was measured using the "Microtrac MT3000" manufactured by Nikkiso Co., Ltd. A suspension containing hydrated titanium dioxide was ultrasonically treated at 30W for 30 seconds using pure water as the measurement solvent, and the particle size distribution was then measured. The 50% volume cumulative particle size was calculated from the obtained particle size distribution and defined as the average secondary particle size.
[0044] (4) Weight reduction rate The weight loss rate was calculated using the "TG / DTA7300" manufactured by Hitachi High-Tech Science Corporation. 10 mg of hydrated titanium oxide was heated from 30°C to 100°C at a rate of 5°C / min in a measurement atmosphere with an airflow of 200 mL / min. The weight loss rate A (%) was calculated from the weight after maintaining the temperature for 2 hours, using the weight before heating as the baseline. Subsequently, the temperature was heated to 250°C at a rate of 5°C / min, and the weight loss rate B (%) was calculated from the weight after maintaining the temperature for 2 hours, using the weight before heating as the baseline. The weight loss rate BA (%) was calculated from the difference between A and B.
[0045] (5) Sulfate ion scavenging capacity 0.5 g of hydrated titanium dioxide was placed in a 100 mL polypropylene bottle, and 50 mL of 0.1 mol / L sulfuric acid aqueous solution was added. The bottle was sealed and shaken at 25°C for 20 hours. The solution was then filtered through a 0.1 μm pore size membrane filter, and the sulfate ion concentration (mg / L) in the filtrate was measured under the following ion chromatography analysis conditions. The same procedure was also performed without hydrated titanium dioxide to measure the sulfate ion concentration (mg / L), and the sulfate ion capture capacity (meq / g) was determined using the following formula (II).
[0046] [Ion chromatography analysis conditions] Measuring instrument: Dionex ICS-2100 Separation column: Dionex IonPacAS11 Guard column: Dionex IonPacAG11 Eluent: 12mM KOH aqueous solution Flow rate: 1.0ml / min Suppressor: ADRS-600 (Recycle Mode)
[0047] Sulfate ion capture capacity (meq / g) = [Sulfate ion concentration in sulfuric acid solution without hydrated titanium oxide (mg / L) - Sulfate ion concentration in sulfuric acid solution after scavenging with hydrated titanium oxide (mg / L)] × 50 / 1000 (L) ÷ Molar mass of sulfate ions (g / mol) × Ionic charge ÷ Mass of hydrated titanium oxide used (g) (II)
[0048] (6) Chloride ion capture capacity 0.5 g of hydrated titanium dioxide was placed in a 100 mL polypropylene bottle, and 50 mL of 0.1 mol / L hydrochloric acid aqueous solution was added. The bottle was sealed tightly and shaken at 25°C for 20 hours. The solution was then filtered through a 0.1 μm pore size membrane filter, and the chloride ion concentration (mg / L) in the filtrate was measured using the ion chromatography analysis conditions described above. The same procedure was also performed without hydrated titanium dioxide to measure the chloride ion concentration (mg / L), and the chloride ion capture capacity (meq / g) was determined using the following formula (III).
[0049] Chloride ion capture capacity (meq / g) = [Hydrochloride ion concentration in hydrochloric acid solution without hydrated titanium oxide (mg / L) - Hydrochloride ion concentration in hydrochloric acid solution after scavenging chloride ions with hydrated titanium oxide (mg / L)] × 50 / 1000 (L) ÷ Molar mass of chloride ions (g / mol) × Ion valence ÷ Mass of hydrated titanium oxide used (g) (III)
[0050] (7) Nitrate ion capture capacity 0.5 g of hydrated titanium dioxide was placed in a 100 mL polypropylene bottle, and 50 mL of 0.1 mol / L nitric acid aqueous solution was added. The bottle was sealed tightly and shaken at 25°C for 20 hours. The solution was then filtered through a 0.1 μm pore size membrane filter, and the nitrate ion concentration (mg / L) in the filtrate was measured using the ion chromatography analysis conditions described above. The same procedure was also performed without hydrated titanium dioxide to measure the nitrate ion concentration (mg / L), and the nitrate ion capture capacity (meq / g) was determined using the following formula (IV).
[0051] Nitrate ion capture capacity (meq / g) = [Nitrate ion concentration in nitric acid solution without hydrated titanium dioxide (mg / L) - Nitrate ion concentration in nitric acid solution after nitrate ion capture with hydrated titanium dioxide (mg / L)] × 50 / 1000 (L) ÷ Molar mass of nitrate ions (g / mol) × Ion valence ÷ Mass of hydrated titanium dioxide used (g) (IV)
[0052] (8) Phosphate ion scavenging capacity 0.5 g of hydrated titanium dioxide was placed in a 100 mL polypropylene bottle, and 50 mL of 0.1 mol / L phosphoric acid aqueous solution was added. The bottle was sealed tightly and shaken at 25°C for 20 hours. The solution was then filtered through a 0.1 μm pore size membrane filter, and the phosphate ion concentration (mg / L) in the filtrate was measured using the ion chromatography analysis conditions described above. The same procedure was also performed without hydrated titanium dioxide to measure the phosphate ion concentration (mg / L), and the phosphate ion capture capacity (meq / g) was determined using the following formula (V).
[0053] Phosphate ion capture capacity (meq / g) = [Phosphate ion concentration in phosphoric acid aqueous solution without hydrated titanium dioxide (mg / L) - Phosphate ion concentration in phosphoric acid aqueous solution after phosphate ion capture with hydrated titanium dioxide (mg / L)] × 50 / 1000 (L) ÷ Molar mass of phosphate ions (g / mol) × Ion valence ÷ Mass of hydrated titanium dioxide used (g) (V)
[0054] (9) Acetate ion capture capacity 0.5 g of hydrated titanium dioxide was placed in a 100 mL polypropylene bottle, and 50 mL of 0.1 mol / L aqueous acetic acid solution was added. The bottle was sealed and shaken at 25°C for 20 hours. The solution was then filtered through a 0.1 μm pore size membrane filter, and the acetate ion concentration (mg / L) in the filtrate was measured using the ion chromatography analysis conditions described above. The same procedure was also performed without hydrated titanium dioxide to measure the acetate ion concentration (mg / L), and the acetate ion capture capacity (meq / g) was determined using the following formula (VI).
[0055] Acetate ion capture capacity (meq / g) = [Acetate ion concentration in acetic acid solution without hydrated titanium dioxide (mg / L) - Acetate ion concentration in acetic acid solution after hydrated titanium dioxide is added to capture acetate ions (mg / L)] × 50 / 1000 (L) ÷ Molar mass of acetate ions (g / mol) × Ion valence ÷ Mass of hydrated titanium dioxide used (g) (VI)
[0056] (10) Sulfate ion capture rate in epoxy resin 60 parts spherical silica, 19.5 parts bisphenol epoxy resin (epoxy equivalent 190), 19.5 parts acid anhydride curing agent (methyl-5-norbornene-2,3-dicarboxylic acid anhydride, molecular weight 178), 1 part hydrated titanium dioxide, 0.1 parts 3-mercaptopropyltrimethoxysilane, and 0.04 parts curing accelerator (2,4,6-tris(dimethylaminomethyl)phenol) were combined and mixed in a rotary-orbit mixer (THINKY Co., Ltd. "Awatori Rentaro ARE-400TWIN"). The mixed resin was placed in a polypropylene container and cured at 100°C, then pulverized. 50g of ion-exchanged water was added to 5g of the pulverized material, and sulfate ions were extracted under conditions of 120°C for 20 hours. Subsequently, this solution was filtered through a membrane filter with a pore size of 0.1 μm, and the sulfate ion concentration (mg / L) in the filtrate was measured under the above ion chromatography analysis conditions. The sulfate ion capture rate was evaluated by dividing this sulfate ion concentration by the value obtained by performing the same procedure without adding hydrated titanium dioxide and measuring the sulfate ion concentration.
[0057] (11) Sulfate ion capture rate in silicone rubber 98.4 parts silicone rubber (Shin-Etsu Chemical Co., Ltd., KE-12), 0.5 parts curing agent (Shin-Etsu Chemical Co., Ltd., CAT-RM), 1 part hydrated titanium dioxide, and 0.1 parts 3-mercaptopropyltrimethoxysilane were mixed together using a rotary-orbit mixer (THINKY Co., Ltd., "Awatori Rentaro ARE-400TWIN"). The mixed rubber was placed in a polypropylene container and cured at 25°C, after which it was pulverized. 50g of ion-exchanged water was added to 5g of the pulverized material, and sulfate ions were extracted under conditions of 120°C for 20 hours. Subsequently, this solution was filtered through a membrane filter with a pore size of 0.1 μm, and the sulfate ion concentration (mg / L) in the filtrate was measured using the above ion chromatography analysis conditions. The sulfate ion capture rate was evaluated by dividing this sulfate ion concentration by the value obtained by performing the same procedure without hydrated titanium dioxide.
[0058] (12) Ionic impurity content 5.0 g of hydrated titanium dioxide was placed in a 100 mL sealed pressure-resistant polytetrafluoroethylene container, and 50 mL of pure water was added. The container was then sealed and treated at 125°C for 20 hours. After cooling, the solution was filtered through a 0.1 μm pore size membrane filter, and the chloride ion, nitrate ion, and sulfate ion concentrations in the filtrate were measured using the ion chromatography analysis conditions described above. Sodium ion and potassium ion concentrations were measured using an ICP emission spectrometer. The sum of these measured values multiplied by 1 / 1000 was used as the ionic impurity content (weight %).
[0059] (13) Assessment of variance 60 parts bisphenol epoxy resin (epoxy equivalent 190) and 40 parts hydrated titanium dioxide were mixed in a rotary-orbit mixer (THINKY Co., Ltd. "Awatori Rentaro ARE-400TWIN"). This mixture was placed on a grindometer (Taiyu Kikai Co., Ltd. "No. 109"), and the mixture on the gauge was scraped off with a metal scraper. The scale was read at the position where 5 to 10 dots of granular marks, created by the movement of the scraper, appeared within a 3 mm wide band.
[0060] (14) Number of bubbles (voids) 50 parts bisphenol epoxy resin (epoxy equivalent 190), 50 parts acid anhydride-based curing agent (methyl-5-norbornene-2,3-dicarboxylic acid anhydride, molecular weight 178), 50 parts spherical silica, 1 part curing accelerator (2,4,6-tris(dimethylaminomethyl)phenol), and 1 part hydrated titanium dioxide were mixed together using a rotation-and-revolution type mixer (THINKY Co., Ltd. "Awatori Rentaro ARE-400TWIN"). The mixed resin was placed in a polypropylene container and cured at 100°C to obtain a cured resin composition. The number of air bubbles (voids) present in a 5 mm square area of each obtained cured resin composition was observed using an optical microscope.
[0061] (15) Corrosion assessment A paste with 70% solid content was made by adding deionized water to hydrated titanium dioxide and applied to a 2cm square copper foil. This was placed in an ESPEC Corporation high-power constant temperature and humidity chamber at 130°C and 85% relative humidity for two days, and the corrosion status of the applied surface was checked. ○ indicates that no corrosion was observed, and if corrosion was observed and the corroded area was 1mm², 2 Less than 1mm is indicated by △. 2 The above cases were evaluated as ×.
[0062] Example 1 500 mL of deionized water at 25°C was stirred, and 200 mL of titanyl sulfate aqueous solution (TM solution, manufactured by Teika Co., Ltd., TiO2 content: 248 g / L) and 250 mL of 28% by mass aqueous ammonia (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were added to obtain a precipitate. At this time, the titanyl sulfate aqueous solution and aqueous ammonia were added dropwise simultaneously so that each was added over 3 hours, and the mixture was stirred for 1 hour after the completion of the dropwise addition. Neutralization was carried out while maintaining the pH of the reaction system at 7.5, and the maximum liquid temperature was 40°C. The solid content concentration of the slurry at this time (measured under dry conditions at 100°C) was 8%. The obtained precipitate was filtered, and the filtrate was filtered with deionized water until the conductivity of the filtrate was 100 μS / cm. The resulting cake was washed and vacuum-dried at 100°C for 12 hours. The dried powder was ground using an ultracentrifuge (Retsch ZM-200) at a rotor speed of 16,000 rpm to obtain the hydrated titanium oxide of Example 1.
[0063] Example 2 In Example 1, the hydrated titanium oxide of Example 2 was obtained using the same method as in Example 1, except that the rotor speed of the ultracentrifuge (Retsch "ZM-200") was set to 12,000 rpm.
[0064] Example 3 In Example 1, the hydrated titanium oxide of Example 3 was obtained using the same method as in Example 1, except that the rotor speed of the ultracentrifugal grinder (Retsch "ZM-200") was set to 8000 rpm.
[0065] Example 4 In Example 1, the hydrated titanium oxide of Example 4 was obtained using the same method as in Example 1, except that the rotor speed of the ultracentrifuge (Retsch "ZM-200") was set to 6000 rpm.
[0066] Example 5 In Example 1, the hydrated titanium oxide of Example 5 was obtained in the same manner as in Example 1, except that the liquid temperature of the ion-exchanged water was maintained at 95°C.
[0067] Example 6 In Example 6, hydrated titanium oxide was obtained using the same method as in Example 1, except that instead of vacuum drying at 100°C, it was dried at 250°C for 6 hours.
[0068] Example 7 In Example 1, hydrated titanium oxide of Example 7 was obtained by the same method as in Example 1, except that instead of vacuum drying at 100°C, drying was performed at 350°C for 6 hours.
[0069] Example 8 In Example 1, hydrated titanium oxide of Example 8 was obtained by the same method as in Example 1, except that instead of vacuum drying at 100°C, drying was performed at 450°C for 6 hours.
[0070] Example 9 In Example 1, the hydrated titanium oxide of Example 9 was obtained using the same method as in Example 1, except that instead of vacuum drying at 100°C, it was vacuum dried at 80°C for 12 hours.
[0071] Example 10 In Example 1, the hydrated titanium oxide of Example 10 was obtained by the same method as in Example 1, except that instead of washing the filtrate with deionized water until its conductivity was 100 μS / cm, the filtrate was washed until its conductivity was 0.7 mS / cm.
[0072] Example 11 In Example 1, the hydrated titanium oxide of Example 11 was obtained by the same method as in Example 1, except that instead of washing the filtrate with deionized water until its conductivity was 100 μS / cm, the filtrate was washed until its conductivity was 2.0 mS / cm.
[0073] Example 12 100 g of hydrated titanium oxide obtained in Example 1 and 5 g of N-phenyl-3-aminopropyltrimethoxysilane (KBM-573, manufactured by Shin-Etsu Chemical Co., Ltd.), a silicon compound, were mixed for 20 minutes in a tabletop blender (LaboMill Surplus, manufactured by Iwatani Corporation). The resulting processed powder was dried in a dryer at 120°C for 2 hours to obtain hydrated titanium oxide coated with a silicon compound. Subsequently, the mixture was pulverized in an ultracentrifuge (ZM-200, manufactured by Lechner) at a rotor speed of 16,000 rpm to obtain the hydrated titanium oxide of Example 12.
[0074] Example 13 In Example 12, the amount of N-phenyl-3-aminopropyltrimethoxysilane (KBM-573, manufactured by Shin-Etsu Chemical Co., Ltd.), which is a silicon compound, was used to 10 g, but the hydrated titanium oxide of Example 13 was obtained in the same manner as in Example 12.
[0075] Example 14 A precipitate was obtained by adding 3 g of deionized water to a mixed solution of 500 mL of ethanol (95%) and 142 g of titanium tetraisopropoxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.). The obtained precipitate was filtered and dried at 80°C. The dried powder was pulverized in an ultracentrifuge (Retsch ZM-200) at a rotor speed of 16,000 rpm to obtain the hydrated titanium oxide of Example 14.
[0076] Example 15 While stirring 500 mL of deionized water, 250 g of an aqueous titanium tetrachloride solution prepared by adding 125 g of titanium tetrachloride (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to deionized water, and 250 mL of 28% by mass aqueous ammonia (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were added to obtain a precipitate. At this time, the titanium tetrachloride and aqueous ammonia were added dropwise simultaneously so that each was added over 3 hours, and the mixture was stirred for 1 hour after the completion of the dropwise addition. Neutralization was carried out while maintaining the pH of the reaction system at 7.5, and the maximum liquid temperature was 40°C. The solid content concentration of the slurry at this time (measured under dry conditions at 100°C) was 8%. The obtained precipitate was filtered, and the filtrate was filtered with deionized water until the conductivity of the filtrate was 500 μS / cm. The resulting cake was washed and vacuum dried at 100°C for 12 hours. The dried powder was pulverized in an ultracentrifuge (Retsch "ZM-200") at a rotor speed of 16000 rpm to obtain hydrated titanium oxide of Example 15.
[0077] Example 16 In Example 16, hydrated titanium oxide was obtained in the same manner as in Example 15, except that instead of washing the filtrate with deionized water until its conductivity was 500 μS / cm, the filtrate was washed until its conductivity was 100 μS / cm.
[0078] Example 17 500 mL of deionized water at 70°C was stirred, and 200 mL of titanyl sulfate aqueous solution (TM solution, manufactured by Teika Co., Ltd., TiO2 content: 248 g / L) and 250 mL of 28% by mass aqueous ammonia (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were added to obtain a precipitate. At this time, the titanyl sulfate aqueous solution and aqueous ammonia were added dropwise simultaneously so that each was added over 3 hours, and the mixture was stirred for 1 hour after the completion of the dropwise addition. Neutralization was carried out while maintaining the pH of the reaction system at 7.5, and the maximum liquid temperature was 80°C. The solid content concentration of the slurry at this time (measured under dry conditions at 100°C) was 8%. The obtained precipitate was filtered, and the filtrate was filtered with deionized water until the conductivity of the filtrate was 100 μS / cm. The resulting cake was washed and vacuum dried at 100°C. The dried powder was pulverized in an ultracentrifuge (Retsch "ZM-200") at a rotor speed of 16000 rpm to obtain hydrated titanium oxide of Example 17.
[0079] Comparative Example 1 Hydrated titanium oxide of Comparative Example 1 was obtained in the same manner as in Example 1, except that instead of vacuum drying at 100°C, heating and calcination were performed at 480°C for 6 hours.
[0080] Comparative Example 2 Hydrated titanium oxide of Comparative Example 2 was obtained in the same manner as in Example 1, except that instead of vacuum drying at 100°C, heating and calcination were performed at 500°C for 6 hours.
[0081] Comparative Example 3 Hydrated titanium oxide represented as TiO(OH)2 (AMT-600, manufactured by Teika Co., Ltd., specific surface area 89 m²) 2 / g, total pore volume 0.2cm³ 3 The hydrated titanium oxide ( / g, average secondary particle size 5 μm) was used for Comparative Example 3.
[0082] [Table 1]
[0083] [Table 2]
Claims
1. A titanium oxide hydroxide having an anion trapping function and a specific surface area of 100 m 2 / g or more and the total pore volume is 0.2 cm 3 / g or more.
2. 2. The hydrous titanium oxide according to claim 1, wherein in an X-ray diffraction measurement, no diffraction peak intensity is detected at a diffraction angle (2θ) of 25.3±0.5°, or the half-value width of a diffraction peak at a diffraction angle (2θ) of 25.3±0.5° is 1.0° or more.
3. 3. The hydrous titanium oxide according to claim 1, having an average secondary particle size of 100 μm or less.
4. 3. The hydrous titanium oxide according to claim 1, wherein a weight loss rate A % calculated from the weight after being held at 100°C for 2 hours and a weight loss rate B % calculated from the weight after being held at 250°C for 2 hours, based on the weight before heating, satisfy the following formula (I): B-A≦15 (I)
5. 3. The hydrous titanium oxide according to claim 1, which has an ionic impurity content of 4.0% by weight or less, or a chlorine content of 200 ppm or less.
6. 3. The hydrous titanium oxide according to claim 1, which has a sulfate ion trapping capacity of 0.20 meq / g or more.
7. 3. The hydrous titanium oxide according to claim 1, which has a chloride ion trapping capacity of 0.02 meq / g or more.
8. 3. The hydrous titanium oxide according to claim 1, further comprising a silicon compound.
9. 3. The hydrous titanium oxide according to claim 1, which is coated with a silicon compound.
10. A resin composition for sealing material, comprising the hydrous titanium oxide according to claim 1 or 2.
11. 3. The method for producing hydrous titanium oxide according to claim 1 or 2, comprising the steps of: using a titanium-containing acidic aqueous solution as a starting material; mixing the titanium-containing acidic aqueous solution with water and a basic aqueous solution at 5 to 98°C to obtain a hydrous titanium oxide precipitate; filtering the titanium precipitate and washing until the electrical conductivity of the filtrate is 2000 μS / cm or less; drying at 100 to 450°C; and pulverizing the hydrous titanium oxide powder after drying.
12. 3. The method for producing hydrous titanium oxide according to claim 1 or 2, characterized in that the method comprises the steps of: using titanium alkoxide as a starting material; obtaining a hydrous titanium oxide precipitate by adding water to an alcohol mixed solution containing the titanium alkoxide so that the molar ratio of the titanium alkoxide to the water (water / titanium alkoxide) is 0.1 or more; filtering the precipitate; drying at 60 to 450° C.; and pulverizing the hydrous titanium oxide powder after drying.